The Role of Transformational Leadership and Communication in Building Good Governance in Indonesia Film Censorship Institution - Taufan Teguh Akbari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2023)
The Film Censorship Institute (LSF) is an institution that has the authority to determine which films are allowed. LSF authority is contained in Government Regulation No. 18 of 2014, where they play a role in protecting the public from negative films that can affect the cultural perspective of the community. LSF adapts to the social and cultural norms that apply in society, so if we look at film censorship institutions in other countries, the scope of films allowed is also different. For example, in the United States, films featuring sexual scenes are permitted, while in Malaysia, they are not. Likewise, films with sexual nuances and extreme violence are not allowed in Indonesia. LSF has also banned the screening of several films because they are not under social rules and norms. However, the work carried out by LSF is rarely known by the public, ranging from their working methods and institutional leadership to how they carry out their work programs. With this background, the author wants to know and understand the practice of good governance in Indonesia Censorship Film Institution and how the transformative approach is taken to bring about change in the organization. This study will use a qualitative approach with data collection through the Focus Group Discussion (FGD) method and literature. The study found that transformative leadership accelerates changes in the LSF by creating innovations for better performance and making an inclusive work culture. This transformative leadership also tremendously affects how LSF implements good governance principles, and all indicators have been fulfilled. The relation and effect of transformative leadership and good governance are also discussed.